2019
DOI: 10.2337/cd18-0020
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the Stigma of Diabetes in Medical Education: A Contact-Based Educational Approach

Abstract: IN BRIEF In this feasibility study, we evaluated the impact of a contact-based education patient panel in an Endocrine and Metabolism course on second-year medical students’ diabetes attitudes and diabetes stigma. Prior to the patient panel, some medical students harbored stigma toward people with diabetes, thus confirming patients’ reports in the literature of diabetes stigma on the part of health care professionals. Importantly, the one-time contact-based educational approach improved students’ di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…The current results suggest that interventions related to psychological health in the context of diabetes should consider, and possibly be tailored, to address weight stigma concerns unique to each diabetes type. Interventions and discussions to mitigate such stigma have been ongoing, citing the need for education and media to focus on correcting misconceptions about what causes diabetes and obesity, and how the two relate to each other [ 30 , 34 , 35 ]. Going forward, research on this disease should mobilize efforts towards stigma reduction, especially for subgroups where it may be most prevalent and most detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…The current results suggest that interventions related to psychological health in the context of diabetes should consider, and possibly be tailored, to address weight stigma concerns unique to each diabetes type. Interventions and discussions to mitigate such stigma have been ongoing, citing the need for education and media to focus on correcting misconceptions about what causes diabetes and obesity, and how the two relate to each other [ 30 , 34 , 35 ]. Going forward, research on this disease should mobilize efforts towards stigma reduction, especially for subgroups where it may be most prevalent and most detrimental.…”
Section: Discussionmentioning
confidence: 99%
“…Patient panels have been shown to reduce stigma toward patients with diverse medical conditions, including diabetes and OUD. 30 , 31 In the patient panel described by Dumenco et al, 31 students from all disciplines reported high rates of attitude change toward people with OUD after hearing from people with lived experience. The patient panel has become a critical component of our OUD education across the curriculum which always elevates people who use drugs as experts in their own health.…”
Section: Discussionmentioning
confidence: 99%
“…Consent occurred online. As in previous studies conducted by the research team [ 26 30 ], participants clicked a radio button indicating “Yes, I consent to participate in this study. I may withdraw my participation at any time.“ Conversely, if participants declined to participate, they clicked a radio button indicating “I decline to participate.“ Both the online welcome screen for the survey and the informed consent document specified the voluntary nature of participation.…”
Section: Methodsmentioning
confidence: 99%